2017
DOI: 10.1007/s12630-017-0820-5
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic considerations for patients with esophageal achalasia undergoing peroral endoscopic myotomy: a retrospective case series review

Abstract: Carbon dioxide insufflation during POEM produces systemic CO uptake and increased intra-abdominal pressure. Changes in cardiorespiratory parameters include increased p, etCO, MAP, and HR. Hyperventilation and PND help mitigate some of these changes. Subcutaneous emphysema is common and may delay extubation and prolong PACU stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 27 publications
4
27
0
Order By: Relevance
“…However, some reports have concluded that while subcutaneous emphysema, mediastinal emphysema and pneumoperitoneum were common during POEM, these did not cause serious complications and no special intervention was required[ 18 , 19 ]. In the previous five reports[ 9 - 13 ], EtCO 2 increased during POEM, but no case of ventilatory impairment occurred. Our report is the first one describing ventilatory impairment during POEM.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, some reports have concluded that while subcutaneous emphysema, mediastinal emphysema and pneumoperitoneum were common during POEM, these did not cause serious complications and no special intervention was required[ 18 , 19 ]. In the previous five reports[ 9 - 13 ], EtCO 2 increased during POEM, but no case of ventilatory impairment occurred. Our report is the first one describing ventilatory impairment during POEM.…”
Section: Discussionmentioning
confidence: 83%
“…Until now, there have been five reports of the anesthetic management of POEM[ 9 - 13 ]. These are summarized in Table 4 .…”
Section: Discussionmentioning
confidence: 99%
“…In this case, anesthesia induced normally could lead to aspiration. To prevent aspiration, it is recommended that rapid induction with cricoid pressure be used and extra caution be taken to prevent regurgitation from the esophagus into the oropharynx …”
Section: Clinical Questions and Statementsmentioning
confidence: 99%
“…Preoperative fasting is usually 8 h in principle, but recently, it is recommended to allow 6 h for light meal and 2 h for clear liquid recently.11 However, no guideline exists for anesthesia management and pre-fasting time for POEM to date. In a recent case series on POEM anesthesia management, fasting times were reported to range from 8 h to 48 h [12-15]. Whether esophagogastroduodenoscopy (EGD) should be performed prophylactically to remove food that may remain in the esophagus is controversial.…”
Section: Fastingmentioning
confidence: 99%
“…Whether esophagogastroduodenoscopy (EGD) should be performed prophylactically to remove food that may remain in the esophagus is controversial. Prophylactic EGD was performed in two case series [12,15], but not in the other two series [13,14]. One case series without prophylactic EGDs recognized the need for it [14], and the other claimed that prophylactic EGD itself was not necessary as it increased the patient’s risk of aspiration [13].…”
Section: Fastingmentioning
confidence: 99%